Majlis Perbandaran Penampang / Magdalen Julius - Julius, Magdalen (Faculty of Business and Management, 2025)
I got the opportunity to work in the Unit Akaun under the Pembangunan Luar Bandar dan Komuniti division while I was an intern at Majlis Perbandaran Penampang. Writing letters, responding to public requests and enquiries, managing daily office clerical tasks, updating cash flows, creating reports, creating monthly balance sheets, verifying and guaranteeing accuracy in warrant payment documents for contractors who completed government construction for development projects, among others were all part of my main duties. I gained practical knowledge in the financial and administrative workings of a government organisation through these job duties. As part of my report, I conducted a SWOT analysis to evaluate the organization’s performance. Majlis Perbandaran Penampang has several strengths, including Excellent Financial Management Strategies and Professional Team and Strong Leadership. However, I identified weaknesses such as Budget Constraints along with Outdated Office Procedures and Technology. On the positive side, the organization has opportunities of Advancing Digital Transformation for MPP and Public Services and Building MPP’s Positive Reputation Impact through Improved Public Services. However, threats such as Allocation of Budget Uncertainty and Increasing Public Expectation Possibly Causing Dissatisfaction may pose challenges to the organisation. I learnt a lot about public administration from my internship and discovered how crucial precision, efficiency and strategic planning are to sustaining successful operations. My internship experience also made me realise how important it is to keep improving in order to overcome challenges and adapt to changing situations. In addition to improving my practical abilities, it also helped me better understand how government organizations like the municipal council operate to benefit the public. Overall, it has been a very honoring and educational experience.